The impact of the current public sector procurement system on the consulting engineering industry - Moos, Moegamat Fatgie (Department of Civil Engineering, 2018)
The development of infrastructure in our country is seen as key to eliminating poverty and reducing inequality. This is confirmed by the establishment of the Presidential Infrastructure Coordinating Council who will coordinate the implementation of the 18 Strategic Infrastructure Projects as part of government's programme. For this infrastructure development programme to be successful, competent engineering professionals are needed. The engineering industry is currently in crisis due mainly to the effect the current public sector procurement system has had on it. The procuring of consulting engineering services is currently done primarily by competitive tendering where price is the deciding factor in the award of tenders. Tenders are evaluated solely on the basis of price and Broad Based Black Economic Empowerment requirements (also known as preference requirements). The criteria for expertise, experience and capacity are only used as qualifying criteria after which price and preference are used for the evaluation. This process is irrespective of the scale of the project or the skills required. The processes are governed by legislation such as the Public Finance Management Act, Preferential Procurement Policy Framework Act and the Municipal Finance Management Act. All public sector institutions and public entities are therefore governed by this and must ensure compliance. There has however been an acknowledgement on the part of government that the current system needs to be reviewed. National Treasury published the Public Sector Supply Chain Management Review in February 2015. This frank look at the current Supply Chain Management system highlighted the shortfalls and what is required to be done to improve the system. The important acknowledgement out of this review is that construction procurement is different to normal procurement and different systems should apply. Despite the initiatives launched by government the current procurement system for consulting engineering services remains unchanged and primarily price driven. Respondents in the private and public sectors were surveyed for their views on the current state of procurement. From the research it is clear that respondents both in the private and public sectors indicate that competition based on price should be changed. Due to low fees tendered consultants no longer have the luxury of seconding senior experienced staff to projects for extended periods of time. Training, development and mentoring of graduate staff has also become less and firms have limited ability to reinvest for growth. Public sector clients' perceptions also indicate that consultants' quality of service has deteriorated. In order to arrest the current situation the study recommends that clarity be sought on the relevant sections of the constitution dealing with procurement. Once this is achieved the National Treasury and the National Department of Trade and Industry should be engaged to get the applicable legislation amended to accommodate a quality and cost based selection system and that takes into account the scale and complexity of projects. This will lead to consultants getting paid fees commensurate with the effort required to execute projects thereby allowing consultants to reinvest in their businesses that will ensure its longevity. This will contribute positively to the infrastructure development required to eliminate poverty, reduce inequality and grow the economy.